Molecular and functional characterization of two isoforms of chalcone synthase and their expression analysis in relation to flavonoid constituents in Grewia asiatica L. - Tareq A Wani; Shahzad A Pandith; Ajai P Gupta; Suresh Chandra; Namrata Sharma; Surrinder K Lattoo (PLoS ONE, 2017)
Chalcone synthase constitutes a functionally diverse gene family producing wide range of flavonoids by catalyzing the initial step of the phenylpropanoid pathway. There is a pivotal role of flavonoids in pollen function as they are imperative for pollen maturation and pollen tube growth during sexual reproduction in flowering plants. Here we focused on medicinally important fruit-bearing shrub Grewia asiatica. It is a rich repository of flavonoids. The fruits are highly acclaimed for various putative health benefits. Despite its importance, full commercial exploitation is hampered due to two drawbacks which include short shelf life of its fruits and larger seed volume. To circumvent these constraints, seed abortion is one of the viable options. Molecular interventions tested in a number of economic crops have been to impair male reproductive function by disrupting the chalcone synthase (CHS) gene activity. Against this backdrop the aim of the present study included cloning and characterization of two full-length cDNA clones of GaCHS isoforms from the CHS multigene family. These included GaCHS1 (NCBI acc. KX129910) and GaCHS2 (NCBI acc. KX129911) with an ORF of 1176 and 1170 bp, respectively. GaCHSs were heterologously expressed and purified in E. coli to validate their functionality. Functionality of CHS isoforms was also characterized via enzyme kinetic studies using five different substrates. We observed differential substrate specificities in terms of their Km and Vmax values. Accumulation of flavonoid constituents naringenin and quercetin were also quantified and their relative concentrations corroborated well with the expression levels of GaCHSs. Further, our results demonstrate that GaCHS isoforms show differential expression patterns at different reproductive phenological stages. Transcript levels of GaCHS2 were more than its isoform GaCHS1 at the anthesis stage of flower development pointing towards its probable role in male reproductive maturity.